Über die Verteilung der Primzahlen des imaginär-quadratischen Zahlkörpers in den Sektoren - Vaitkevičius, J. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. Вайткявичус. О распределении простых чисел мнимого квадратного поля в секторахJ. Vaitkevičius. Apie menamo kvadratinio skaičių kūno pirminių skaičių pasiskirstymų sektoriuose